Virulence Phenotypes and Molecular Genotypes in Collections of Puccinia triticina from Italy - Mantovani, Paola (Plant disease, 2010)
Twenty-four isolates of Puccinia triticina from Italy were characterized for virulence to seedlings of 22 common wheat Thatcher isolines, each with a different leaf rust resistance gene, and for molecular genotypes at 15 simple sequence repeat (SSR) loci. The isolates were compared to a set of 13 previously characterized P. triticina isolates from either durum or common wheat. Clustering based on virulence phenotypes and SSR genotypes grouped the Italian P. triticina isolates into three groups. In the first group, the isolates had virulence phenotypes and SSR genotypes that were similar to the isolates collected from durum wheat. Isolates in the second group were unique because they had virulence similar to the isolates from common wheat but were distinct for SSR genotypes compared to the isolates from durum wheat and from common wheat. Isolates in the third group had virulence phenotypes and SSR genotypes closely related to the isolates from common wheat. The isolates were grouped based on the known or assumed host of origin, virulence phenotype, and SSR genotypes. Measures of FST and RST for SSR genotypes, and ΦST for virulence phenotype were significant, which indicated differentiation among the three groups of isolates. Virulence phenotypes and molecular genotypes were highly correlated with r = 0.74